Convergência de conjuntos de bases em cálculos de polarizabilidade de dipolo estática de aglomerados de metais alcalinos - Souza, Fábio Arthur Leão de (2013)
An hierarchical sequence of all-electron segmented contracted basis sets of double, triple, and quadruple zeta valence qualities plus polarization functions augmented with di use functions for the atoms from H to Ar was constructed by Jorge et al. A systematic study of basis sets required to obtain reliable and accurate values of static dipole polarizabilities of lithium and sodium clusters ( n=2,4,6, and 8 ) at their optimized equilibrium geometries is reported. Three methods are examined: Hartree-Fock (HF), second order Mfller-Plesset perturbation theory (MP2), and density functional theory (DFT). By direct calculations or by tting the directly calculated values through one extrapolation scheme, estimates of the HF, MP2, and DFT complet basis set limits have been obtained. Comparasion with experimental and theoretical data reported previously in the literature is done